Oral feeding challenges of infants of diabetic mothers - Dietrich, Leslie-Anne J. (Frontiers in Pediatrics, 2024)
Objective: The presence of diabetes before or during pregnancy can increase perinatal mortality and morbidities. It is well known an infant of a diabetic mother (IDM) may experience complications such as macrosomia, hypoglycemia, respiratory distress syndrome, cardiac anomalies, and other abnormalities of organogenesis. Medical providers including physicians, nurses, and speech therapists have experienced challenges with helping IDMs orally feed. Challenges with oral feeding can lead to prolonged hospital stays and placement of supplemental feeding devices. The etiology of an IDM’s oral feeding delays is not well understood and does not necessarily affect all infants. Study Design: This descriptive review explores what is known about potential contributing factors to feeding difficulty in IDMs, including differences in infant behavior and swallowing mechanics. Results: Some IDMs are unable to maintain active alert states and have decreased autonomic regulation and motor control. Studies of sucking and swallowing demonstrate reduced sucking pressure, fewer sucking bursts, and slowing of esophageal sphincter function. Conclusion: The increasing prevalence of diabetes during pregnancy makes further investigations into the